Pengaruh Bauran Pemasaran Terhadap Peningkatan Penjualan Wedding Package di Valika Wedding Organizer Kota Mataram Nusa Tenggara Barat - I Gede Sumadi; I Nengah Wirata (Journal of Event and Convention Management, 2022)
Wedding organizer is a professional service provider in organizing and designing wedding events by making the series of events better and smoother. The desire to be able to compete with other wedding organizers, triggers the sale of wedding packages that make it easier for customers to choose the best wedding event. In order to be able to attract a wider market segmentation, wedding organizer companies should offer their products through a marketing mix strategy This study aims to determine the effect of product, price, place and promotion on the level of sales. The population in this study are customers who have used the services of Valika Wedding Organizer with the sample used as many as 60 respondents. The data analysis technique used in this research is Multiple Linear Regression, Coefficient of Determination, Partial Significance Test (t-test) and Simultaneous Significance Test (F-Test) Based on the results of the study, it can be seen that product has a positive and significant effect on sales levels, price has a significant positive effect on sales levels, place has a significant positive effect on sales levels, promotion has a significant positive effect on sales levels. The magnitude of the influence of product, price, place, promotion and volume of review variables on the level of sales is 60%. Suggestions that can be given by researchers to Valika Wedding Organizer are to make uniforms for crews that have attractive designs, provide bonuses or additional facilities for free, help consumers if they have difficulty finding an office location, always maintain relationships with clients even though the wedding is over and provide respondents fast in serving consumers and always friendly to consumers